LEADERSHIP DYNAMICS AND QUALITY MANAGEMENT: ENHANCING AMIL PERFORMANCE IN ZAKAT INSTITUTIONS - Riski Aseandi; Ulen Bangun; Siti Mujiatun; Meisya Darus (RADJA PUBLIKA, 2026)
This study investigates the influence of transformational and transactional leadership styles on the performance of zakat officers (amil) in zakat institutions in Medan City, with Total Quality Management (TQM) examined as a mediating variable. Utilizing a quantitative approach, data were collected from 31 amil zakat through a structured questionnaire, and analyzed using Structural Equation Modeling (SEM) with SmartPLS to test direct and indirect relationships among variables. The results reveal that both transformational and transactional leadership significantly affect amil performance, but transformational leadership exerts a stronger impact in driving performance and supporting TQM implementation. TQM itself plays a critical mediating role, amplifying the influence of both leadership styles on performance outcomes. These findings suggest that leadership effectiveness in zakat institutions is not solely determined by leaders’ behavior but also depends on the organization’s ability to institutionalize comprehensive quality management practices. The study enriches the understanding that combining visionary, inspirational, and adaptive leadership with a quality-oriented organizational culture is key to fostering professionalism and accountability among amil zakat. This research contributes practically by highlighting the importance of prioritizing transformational leadership supported by consistent TQM application as a relevant strategy to enhance governance, transparency, and public trust in zakat institutions in Medan